Social conflict and agrarian change in Uganda's countryside. (5th July 2019) - Martiniello, Giuliano
Abstract: In this paper, I explore the significance of Giovanni Arrighi's scholarship about the dynamics of capitalist accumulation and transformation in Africa and other "hostile" environments for critical agrarian studies. Specifically, I examine the relevance of his work for the analysis of multiple trajectories of agrarian change and social conflict in Uganda's countryside. By adopting synchronic and diachronic perspectives, the analysis here unveils the geographically uneven nature of transformation in the agrarian social structure in two distinct regions in Uganda: Buganda and Acholi. This complementarity allows us to grasp continuities and discontinuities in the processes of agrarian change and in the social struggles over the production and appropriation of surplus value in the longue durée. I argue that the agrarian social structure and the associated dynamics and forms of social conflict in the two regions massively diverged during the colonial period, while partially converging in the current era of neoliberal restructuring.